A study of Perception and Engagement as a response of Consumers towards ads on Facebook and Google search engine - Usman, Mohammed (Archives of Business Research, 2020)
Inbound marketing induces a customer to buy a product online by search engine optimization or various digital marketing strategies. Pull marketing is a proven way of attracting customers towards brands and engaging them for buying. Perceptions make an individual to either make a good image or bad image of the product. Buying products is a click away. Digital marketing is making reforms in India which are already doing well in foreign countries. India is witnessing a growth of internet usage due to digital marketing reforms, companies are using online marketing strategies to get them attracted towards their businesses. The online advertisement makes an individual to make the perception of the product and then respond in the form of clicking, liking sharing the social media content and then buying the product. The study will consider the demographic factors age group and gender as two variables for studying the perception of consumers towards social media. The study will help to determine customer engagement as a response to positive percetion of the ads on Facebook and Google search engine results.The engagement of customer is considered to be determined by three factors as browsing,sharing and buying products after getting influenced by ads on facebook and google serach engine results.